ADVERSE SOCIAL COMPARISON PROCESSES AND NEGATIVE SELF-FEELINGS: A TEST OF ALTERNATIVE MODELS - Stiles, Beverly L.; Kaplan, Howard B. (Social behavior and personality, 2004)
Theoretically informed models are estimated that specify the direction of the relationship between social comparisons and negative self-feelings. The data are from three waves of an ongoing longitudinal study of adaptations to stress. Subjects are individuals who were tested in their middle teens (T3), mid-twenties (Time 4) and in their mid-thirties (Time 5). The models were estimated using both logistic regression and ordinary least squares regression. In general, the results suggest that negative self-feelings are an antecedent of social comparison processes as negative self-feelings are significantly related to all five measures of social comparison. Findings suggest that negative self-feelings are sometimes a consequence of social comparison processes as negative self-feelings are significantly related to three of the five measures of social comparison.